Are Investors Warned by Disclosure of Conflicts of Interest? The Moderating Effect of Investment Horizon - Liu, Yuanyuan; Huang, Zhongwei; Jiang, Like; Messier, William F. (The Accounting Review, 2020)
ABSTRACT Financial analysts are required to disclose conflicts of interest (COI) in their research reports, but there is limited evidence on the effectiveness of COI disclosures. We investigate whether the influence of disclosing COI in analyst reports on investors' decision making depends on investment horizon. Experimental results show that short-term investors who view a COI disclosure are significantly less willing to invest in the recommended stock compared to short-term investors who do not view such a disclosure, while the presence of a COI disclosure does not significantly affect long-term investors' willingness to invest. Results further demonstrate that the COI disclosure decreases short-term investors' willingness to invest by reducing their perception of analysts' trustworthiness and expertness. This study provides evidence on when and how the COI disclosure can influence investors' behavior and enhances our understanding of investors' reactions to cautionary disclaimers. Data Availability: Contact the authors.